A Retrospective Analysis of Risk Factors and Impact of Acute Kidney Injury in Critically Ill Children - Celegen, Kubra; Celegen, Mehmet (Klinische Pädiatrie, 2023)
Background Acute kidney injury (AKI) is a serious clinical condition in critically ill children and is associated with worse outcomes. A few pediatric studies focused on the risk factors of AKI. We aimed to identify the incidence, risk factors, and outcomes of AKI in the pediatric intensive care unit (PICU).Patients and methods All the patients admitted to PICU over a period of 20 months were included. We compared both groups the risk factors between AKI and non-AKI.Results A total of 63 patients (17.5%) of the 360 patients developed AKI during PICU stay. The presence of comorbidity, diagnosis of sepsis, increased PRISM III score, and positive renal angina index were found to be risk factors for AKI on admission. Thrombocytopenia, multiple organ failure syndrome, the requirement of mechanical ventilation, use of inotropic drugs, intravenous iodinated contrast media, and exposure to an increased number of nephrotoxic drugs were independent risk factors during the hospital stay. The patients with AKI had a lower renal function on discharge and had worse overall survival.Conclusions AKI is prevalent and multifactorial in critically sick children. The risk factors of AKI may be present on admission and during the hospital stay. AKI is related to prolonged mechanical ventilation days, longer PICU stays, and a higher mortality rate. Based on the presented results early prediction of AKI and consequent modification of nephrotoxic medication may generate positive effects on the outcome of critically ill children.
Keywords: Acute kidney injury; critically ill children; pediatric intensive care unit; risk factors; nephrotoxic medications; renal angina index